Understanding the mushārakah mutanāqiṣah of Koperasi Pembiayaan Syariah Angkasa (KOPSYA) - Norbaizurah Abdul Jabar (ISRA International Journal of Islamic Finance, 2017)
Purpose - In Malaysia, both Islamic financial institutions (IFIs) and Islamic co-operatives (ICs) provide mushārakah mutanāqiṣah (diminishing partnership) (MM) financing. It was initially a preferred contract as it is deemed to be more Sharīʿah-compliant and free from the element of ribā (interest) in comparison to other Sharīʿah-compliant sale contracts. Nevertheless, MM is now considered less appealing to IFIs due to its existing challenges. This paper aims to emphasise on MM as practiced by ICs which will highlight approaches to default, pricing of rental rates, profit sharing method and early settlement which differ to the practice of MM by IFIs. Design/methodology/approach - This study focuses on Koperasi Pembiayaan Syariah Angkasa (KOPSYA), an IC based in Malaysia, which the authors concurred as being an ideal organisation to study on the matter due to its strong stance in promoting Sharīʿah-compliant financing products. Findings - The research highlights the flexibility of MM implementation in KOPSYA to provide some insights on the rationale behind MM operations in KOPSYA. Originality/value - The authors are hopeful that this paper will aspire further interest by giving the readers better understanding on the implementation of MM in KOPSYA and how it will benefit the customers.